The unseen guest - Wood, Maryrose (The incorrigible children of Ashton Place, 2012)
"Miss Penelope Lumley embarks on an investigation into the mysteries surrounding the Incorrigible children, Lord Ashton, the forests of Ashton Place, and her own past"--